Microarray Analysis of Gene Expression Provides New Insights Into Denervation-Induced Skeletal Muscle Atrophy - Shen, Yuntian; Zhang, Ru; Xu, Liang; Wan, Qiuxian; Zhu, Jianwei; Gu, Jing; Huang, Ziwei; Ma, Wenjing; Shen, Mi; Ding, Fei; Sun, Hualin (Frontiers in Physiology, 2019)
Denervation induces skeletal muscle atrophy, accompanied by complex biochemical and physiological changes, with potentially devastating outcomes even an increased mortality. Currently, however, there remains a paucity of effective strategies to treat skeletal muscle atrophy. Therefore, it is required to understand the molecular mechanisms of skeletal muscle atrophy and formulate new treatment strategies. In this study, we investigated the transcriptional profile of denervated skeletal muscle after peripheral nerve injury in rats. The cDNA microarray analysis showed that a huge number of genes in tibialis anterior (TA) muscles were differentially expressed at different times after sciatic nerve transection. Notably, the 24 h of denervation might be a critical time point for triggering TA muscle atrophy. According to the data from self-organizing map (SOM), Perason correlation heatmap, principal component analysis (PCA), and hierarchical clustering analysis, 3 nodal transitions in gene expression profile of the denervated TA muscle might partition the period of 0.25 h-28 d post nerve injury into 4 distinct transcriptional phases, designated as "oxidative stress stage", "inflammation stage", “atrophy stage” and “atrophic fibrosis stage” respectively. Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene ontology (GO) analyses revealed the biological feature of each transcriptional phase. Importantly, the differentially expressed genes at 24 h post sciatic nerve transection seemed to be mainly involved in inflammation, which might be a critical process in denervation-induced muscle atrophy. Overall, our study would contribute to the understanding of molecular aspects of denervation-induced muscle atrophy, and may also provide a new insight into the time window for targeted therapy.